The science of surfing : a Surfside girls guide to the ocean - Dwinell, Kim (Dwinell, Kim. Surfside girls., 2021)
"Have you ever wondered why the ocean has waves? Why do the tides change with the moon? Can dolphins really see using sound? How does surfing actually work? And what can we do to protect the ocean? Cresting from the pages of the beloved graphic novel series Surfside Girls, join best friends Sam & Jade -- and Sam's little brother Peet -- as they explore the AWESOME world of ocean science. From physics to marine biology to ecology to surfing lessons, there's so much to learn... with plenty of fun and jokes along the way! The Science of Surfing is the coolest way to take a beach vacation and learn at the same time." --